The Relationship Between Chronic Hypertension and The Incidence of Spontaneous Abortion in Pregnant Women in RSU Karsa Husada Batu - Lillalamin, Almawaddah Warrahmattan (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
Spontaneous abortion is the condition of the natural end of pregnancy before the fetus can live outside the womb, namely before 20 weeks of gestation or fetal weight less than 500 grams. One of the risk factors that can affect spontaneous abortion is chronic hypertension. Very high blood pressure can interfere with the blood flow needed to support fetal growth and development so that there is a high potential for mothers to experience spontaneous abortion conditions. The incidence of spontaneous abortion at RSU Karsa Husada Batu in the period January 2022 - December 2023 was 139 cases. The purpose of this study was to determine the relationship between chronic hypertension and the incidence of spontaneous abortion in pregnant women at RSU Karsa Husada Batu. This study is an analytical observational study by obtaining data from hospital medical records. The design of this study was cross sectional with a total sample that met the inclusion and exclusion criteria of 50 patients. The data collection technique used non probability sampling technique type purposive sampling. Data analysis using univariate and bivariate analysis. Bivariate data analysis using the Chi Square test with a p-value of 0.000. So it can be stated that there is a significant relationship between chronic hypertension and the incidence of spontaneous abortion. Keywords: Spontaneous Abortion, Chronic Hypertension